2019
DOI: 10.1111/jgs.16242
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnicity, and Other Risks for Live Discharge Among Hospice Patients with Dementia

Abstract: OBJECTIVES The end‐of‐life trajectory for persons with dementia is often protracted and difficult to predict, placing these individuals at heightened risk of live discharge from hospice. Risks for live discharge due to condition stabilization or failure to decline among patients with dementia are not well established. Our aim was to identify demographic, health, and hospice service factors associated with live discharge due to condition stabilization or failure to decline among hospice patients with dementia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…16 Another recent study documented that compared with non-Hispanic White hospice patients with dementia, non-Hispanic Blacks patients with dementia experienced increased risk of live discharge. 177 A qualitative study conducted with non-Hispanic Black patients and lay caregivers receiving hospice care services found additional barriers to hospice enrollment, including 1) inconsistent health care access associated with economic enabling factors; 2) poor communication with providers and perceived experiences of discrimination by the health care system; 3) the bureaucratic difficulty of receiving reimbursement under the Medicare hospice benefit; and 4) the perception that hospice care is a way to abdicate responsibilities or to hasten a person's death. 74 An interesting qualitative study that examined the knowledge, beliefs and attitudes of non-Hispanic Black and White home health clients who were eligible for but refused to enroll in hospice care, found very similar perspectives among both racial groups with regard to attitudes about end-of-life care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Another recent study documented that compared with non-Hispanic White hospice patients with dementia, non-Hispanic Blacks patients with dementia experienced increased risk of live discharge. 177 A qualitative study conducted with non-Hispanic Black patients and lay caregivers receiving hospice care services found additional barriers to hospice enrollment, including 1) inconsistent health care access associated with economic enabling factors; 2) poor communication with providers and perceived experiences of discrimination by the health care system; 3) the bureaucratic difficulty of receiving reimbursement under the Medicare hospice benefit; and 4) the perception that hospice care is a way to abdicate responsibilities or to hasten a person's death. 74 An interesting qualitative study that examined the knowledge, beliefs and attitudes of non-Hispanic Black and White home health clients who were eligible for but refused to enroll in hospice care, found very similar perspectives among both racial groups with regard to attitudes about end-of-life care.…”
Section: Methodsmentioning
confidence: 99%
“… 16 Another recent study documented that compared with non-Hispanic White hospice patients with dementia, non-Hispanic Blacks patients with dementia experienced increased risk of live discharge. 177 …”
Section: Methodsmentioning
confidence: 99%
“…Provider communication is key to engaging older African Americans and their caregivers in EOL conversations. When racist perceptions or even stereotypical thoughts impact the communication process, there is increased risk for miscommunication and breakdown of the process [ 42 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…A study with a cohort of 1212 individuals from the Reasons for Geographic and Racial Difference in Stroke (REGARDS 2003-2007) dataset showed that Blacks were more likely to continue treatment at the EOL and less hospice usage than their White counterparts [41]. For older adults with dementia and the likelihood of live discharge from hospice, two studies found that African Americans weresignificantly more likely to experience a live discharge from hospice than Whites; some of these discharges occurred following acute hospitalizations [42,43]. These findings signify that African Americans experience arduous disruptions in care at EOL resulting in a higher likelihood of them not being able to benefit from these services due to acute hospitalization [43].…”
Section: Hospice and Palliative Carementioning
confidence: 99%
“…8,9 Despite the development and expansion of support for end of life planning, there is unequal utilization of these services based on various sociodemographic factors including race, ethnicity, primary language, urbanization, housing stability and education level. 8,[10][11][12][13][14][15][16] For example, in a qualitative study, Purkey and MacKenzie found that individuals with lived experiences of homelessness and/or substance abuse described barriers within the health care system preventing them from achieving their desired end of life goals. 16 Given the expanding population of older adults, coupled with the growing geographic and socioeconomic diversity, it is imperative that we continue to work to understand the unmet needs for end of life care planning for older adults from diverse populations.…”
Section: Introductionmentioning
confidence: 99%